The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the Eighth Conference on European Chapter of the Association for Computational Linguistics - 1997
DOI: 10.3115/979617.979640
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the semantic orientation of adjectives

Abstract: We identify and validate from a large corpus constraints from conjunctions on the positive or negative semantic orientation of the conjoined adjectives. A log-linear regression model uses these constraints to predict whether conjoined adjectives are of same or different orientations, achieving 82% accuracy in this task when each conjunction is considered independently. Combining the constraints across many adjectives, a clustering algorithm separates the adjectives into groups of different orientations, and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
604
3
20

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 758 publications
(631 citation statements)
references
References 4 publications
4
604
3
20
Order By: Relevance
“…Although many approaches to subjectivity classification focus only on the presence of subjectivity cue words themselves, disregarding context (e.g., Hart (1984), Anderson and McMaster (1982), Hatzivassiloglou and McKeown (1997), Turney (2002), Gordon et al (2003), Yi et al (2003)), the observations in this section suggest that different usages of words, in context, need to be distinguished to understand subjectivity.…”
Section: Ambiguity Of Individual Wordsmentioning
confidence: 95%
See 1 more Smart Citation
“…Although many approaches to subjectivity classification focus only on the presence of subjectivity cue words themselves, disregarding context (e.g., Hart (1984), Anderson and McMaster (1982), Hatzivassiloglou and McKeown (1997), Turney (2002), Gordon et al (2003), Yi et al (2003)), the observations in this section suggest that different usages of words, in context, need to be distinguished to understand subjectivity.…”
Section: Ambiguity Of Individual Wordsmentioning
confidence: 95%
“…Certainly much of the work on identifying subjective expressions in NLP has focused on learning adjectives (e.g., Hatzivassiloglou and McKeown (1997), Wiebe (2000), and Turney (2002)). Among the content words (as defined above) in expressive subjective elements, 14% are adverbs, 21% are verbs, 27% are adjectives, and 38% are nouns.…”
Section: Wide Variety Of Words and Parts Of Speechmentioning
confidence: 99%
“…Prior work has shown that it is possible to generate and extend polarity dictionaries in an unsupervised manner using grammatical [31] or co-occurrence relations [83] between words. By applying these methods on Web data, we can also infer the polarity for slang and common misspellings [84], which improves the quality of opinion mining on, e.g., social media data.…”
Section: Opinion Mining For Culturomicsmentioning
confidence: 99%
“…Subjectivity analysis is defined by Wiebe in (1994), "linguistic expression of somebody's opinions, sentiments, emotions, evaluations, beliefs and speculations" (Wiebe 1994). Hatzivassiloglou and McKeown (1997) analyzed the semantic constraints of conjunction in large-scale corpus to calculate the emotional tendency of adjectives (Hatzivassiloglou and McKeown 1997).…”
Section: Introductionmentioning
confidence: 99%